High hydride count rhodium octahedra, [Rh6(PR3)6H12][BArF4]2: synthesis, structures, and reversible hydrogen uptake under mild conditions. - Brayshaw, S; Ingleson, M; Green, J; McIndoe, J; Raithby, P; Kociok-Köhn, G; Weller, A (2006)
A new class of transition metal cluster is described, [Rh(6)(PR(3))(6)H(12)][BAr(F)(4)](2) (R = (i)Pr (1a), Cy (2a); BAr(F)(4) = [B{C(6)H(3)(CF(3))(2)}(4)](-)). These clusters are unique in that they have structures exactly like those of early transition metal clusters with edge-bridging pi-donor ligands rather than the structures expected for late transition metal clusters with pi-acceptor ligands. The solid-state structures of 1a and 2a have been determined, and the 12 hydride ligands bridge each Rh-Rh edge of a regular octahedron. Pulsed gradient spin-echo NMR experiments show that the clusters remain intact in solution, having calculated hydrodynamic radii of 9.5(3) A for 1a and 10.7(2) A for 2a, and the formulation of 1a and 2a was unambiguously confirmed by ESI mass spectrometry. Both 1a and 2a take up two molecules of H(2) to afford the cluster species [Rh(6)(P(i)Pr(3))(6)H(16)][BAr(F)(4)](2) (1b) and [Rh(6)(PCy(3))(6)H(16)][BAr(F)(4)](2) (2b), respectively, as characterized by NMR spectroscopy, ESI-MS, and, for 2b, X-ray crystallography using the [1-H-CB(11)Me(11)](-) salt. The hydride ligands were not located by X-ray crystallography, but (1)H NMR spectroscopy showed a 15:1 ratio of hydride ligands, suggesting an interstitial hydride ligand. Addition of H(2) is reversible: placing 1b and 2b under vacuum regenerates 1a and 2a. DFT calculations on [Rh(6)(PH(3))(6)H(x)()](2+) (x = 12, 16) support the structural assignments and also show a molecular orbital structure that has 20 orbitals involved with cluster bonding. Cluster formation has been monitored by (31)P{(1)H} and (1)H NMR spectroscopy, and mechanisms involving heterolytic H(2) cleavage and elimination of [HP(i)Pr(3)](+) or the formation of trimetallic intermediates are discussed.